Relationships of human antroduodenal motility and transpyloric fluid movement: non-invasive observations with real-time ultrasound. Issue 12 (December 1984) - King, P M; Adam, R D; Pryde, A; McDicken, W N; Heading, R C
Abstract : To study the relationships between gastric antral and proximal duodenal motor activity, and the movement of liquid across the pylorus, 10 healthy volunteers were given a test meal of dilute orange juice and bran, and events at the gastric outlet monitored by real-time ultrasound. A total of 116 complete gastric peristaltic cycles were observed and in 86% of these, associated proximal duodenal contractions were seen. Transpyloric fluid movement, as reflected by the movement of the bran particles, occurred as brief episodes during the time when the pylorus was open. Distal flow, in episodes lasting 2-4 seconds, was seen to occur in 81% of the 116 complete cycles and 75% of these episodes occurred just after the relaxation of the terminal antrum, pylorus, and proximal duodenum. The remainder occurred shortly before the terminal antral contraction. Retrograde flow, in episodes of up to 5 seconds, occurred in 78% of observed cycles with the majority occurring immediately before contraction of the terminal antrum. Our findings indicate that transpyloric fluid movement occurs in brief episodes lasting a few seconds only and that retrograde flow across the pylorus occurs in normal subjects. This pattern of fluid movement can bear no direct relationship to a steadily advancing antral peristaltic contraction, nor be wholly attributable to constant intragastric pressure.